2022
DOI: 10.5194/acp-22-13355-2022
|View full text |Cite
|
Sign up to set email alerts
|

Responses of CIPS/AIM noctilucent clouds to the interplanetary magnetic field

Abstract: Abstract. This study investigates the link between the interplanetary magnetic field (IMF) By component and the noctilucent clouds (NLCs) measured by the Cloud Imaging and Particle Size (CIPS) experiment onboard the Aeronomy of Ice in the Mesosphere (AIM) satellite. The mean ice particle radius in NLCs is found to be positively correlated with IMF By in the Southern Hemisphere (SH) and negatively correlated with IMF By in the Northern Hemisphere (NH), respectively, on a day-to-day timescale in most of the 20 s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The CMN scheme provides a new pathway for the solar activity to affect PMCs via the charging process of MSPs. Zhang et al (2022) report a positive response of the ice particle radius r, IWC and albedo to the IMF By in the SH with a lag time of about zero days, and an opposite but weak response in the NH. These results are difficult to understand in the GS scheme, however, they are readily explicable in the CMN scheme: the increase in IMF By induces an increase in the electric potential of the ionosphere in the SH, which reduces the concentration of electrons and the negatively charged-MSPs, ultimately leading to an increase in the ice particle radius.…”
Section: New Pathways For Solar Activity and Atmospheric Dynamics Aff...mentioning
confidence: 90%
See 2 more Smart Citations
“…The CMN scheme provides a new pathway for the solar activity to affect PMCs via the charging process of MSPs. Zhang et al (2022) report a positive response of the ice particle radius r, IWC and albedo to the IMF By in the SH with a lag time of about zero days, and an opposite but weak response in the NH. These results are difficult to understand in the GS scheme, however, they are readily explicable in the CMN scheme: the increase in IMF By induces an increase in the electric potential of the ionosphere in the SH, which reduces the concentration of electrons and the negatively charged-MSPs, ultimately leading to an increase in the ice particle radius.…”
Section: New Pathways For Solar Activity and Atmospheric Dynamics Aff...mentioning
confidence: 90%
“…In contrast, the response in the Northern Hemisphere (NH) is opposite (Lam and Tinsley, 2016;Tinsley and Heelis, 1993). Zhang et al (2022) have demonstrated a positive/negative correlation between the IMF By and the ice particle radius of PMCs in the SH/NH with a lag time of about zero days, providing evidence in favor of the charged-MSPs acting as ice nuclei.…”
Section: Nucleation Processes In Pmcsmentioning
confidence: 99%
See 1 more Smart Citation